Strategi Memasyarakatkan Gerakan Koperasi di Indonesia: Pendekatan Edukasi, Digitalisasi, dan Pemberdayaan Berbasis Komunitas - Putri, Fera Islami; Alhidayatullah, Alhidayatullah (PT Alahyan Publisher Sukabumi, 2025)
Cooperatives play a strategic role as a pillar of the people’s economy in Indonesia; however, the cooperative movement continues to face various challenges, including low member participation, limited cooperative literacy, and slow adaptation to digital transformation. This study aims to analyze strategies for popularizing the cooperative movement in Indonesia through educational, digitalization, and community-based empowerment approaches. The study employs a qualitative approach with a descriptive-exploratory research design. Data were collected through in-depth interviews, document analysis, and observations of cooperatives actively implementing member education programs, digital technology utilization, and community empowerment initiatives. Data analysis was conducted using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that education plays a crucial role in enhancing members’ understanding, awareness, and participation in cooperatives, particularly in internalizing cooperative values and principles. Digitalization has been shown to improve operational efficiency, transparency, and competitiveness of cooperatives, although its implementation remains constrained by limited digital literacy and human resource capacity. Meanwhile, community-based empowerment strengthens cooperative sustainability by increasing member participation, reinforcing social capital, and developing businesses based on local potential. This study concludes that the integration of education, digitalization, and community-based empowerment constitutes an effective strategy for popularizing the cooperative movement in Indonesia. The findings are expected to serve as a reference for cooperative practitioners and policymakers in formulating inclusive, adaptive, and sustainable cooperative development strategies.